2015
DOI: 10.14744/nci.2015.25338
|View full text |Cite
|
Sign up to set email alerts
|

An unusual cause of acute abdomen – epiploic appendagitis: report of two cases

Abstract: Epiploic appendices, first described in 1543 by Vesalius, are fatty structures which are attached through the length of the colon and consisted of visceral peritoneum. Epiploic appendicitis is an uncommon and self-limiting disease. In this report, we aimed to present two patients with epiploic appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A clinical profile of 21 patients of EA searched in the indexed journals shows that almost 90% have lower abdominal pain, as shown in Table 1 [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Fever and vomiting were absent in most patients, while tenderness of localized area was present in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical profile of 21 patients of EA searched in the indexed journals shows that almost 90% have lower abdominal pain, as shown in Table 1 [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Fever and vomiting were absent in most patients, while tenderness of localized area was present in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…PEA being a self-limiting disease is managed conservatively with a better understanding of the disease, and conservative management is established as the treatment of choice [ 4 , 5 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The right lower PEA is often confused with acute appendicitis; while left sided PEA is often misdiagnosed as sigmoid diverticulitis in clinic. Therefore, diagnosis of PEA was often the result of an unexpected finding during an exploratory laparotomy in the past [14] . Today, however, this condition is usually accurately diagnosed by Color Doppler ultrasound (CDUS) or CT pre-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the past, the regular therapy for PEA was surgical excision because most cases were discovered during exploratory operation. Some researchers have reported that pain recurred or persisted until the epiploic appendagitis was removed in a part of their cases, so they strongly recommended excision of PEA when it was diagnosed [14] . Later, with the further understanding of this disease, more and more researchers proposed nonsurgical management of PEA.…”
Section: Discussionmentioning
confidence: 99%